2012
DOI: 10.1002/alr.21112
|View full text |Cite
|
Sign up to set email alerts
|

Office‐based balloon sinus dilation: a prospective, multicenter study of 203 patients

Abstract: Performance of ESS with BSD in the office under local anesthesia is feasible, well-tolerated, safe, and effective. Twenty-four week follow-up demonstrates clinical and statistical improvement in patient quality of life and radiographic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 19 publications
5
71
0
7
Order By: Relevance
“…Increasingly complex procedures are now performed in the office, and in 2010, the number of such procedures performed in the United States was estimated at more than 10 million 1. Balloon catheter dilation (BCD) of paranasal sinuses in the treatment of patients with chronic rhinosinusitis (CRS) who experience an inadequate response to medical management is an example of such a procedure 2. Before the introduction of BCD in 2005, nearly all sinus surgeries were performed in operating rooms, under general anesthesia, as rigid instruments were required to create access within diseased tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly complex procedures are now performed in the office, and in 2010, the number of such procedures performed in the United States was estimated at more than 10 million 1. Balloon catheter dilation (BCD) of paranasal sinuses in the treatment of patients with chronic rhinosinusitis (CRS) who experience an inadequate response to medical management is an example of such a procedure 2. Before the introduction of BCD in 2005, nearly all sinus surgeries were performed in operating rooms, under general anesthesia, as rigid instruments were required to create access within diseased tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Before the introduction of BCD in 2005, nearly all sinus surgeries were performed in operating rooms, under general anesthesia, as rigid instruments were required to create access within diseased tissue. Sinus surgery using BCD tools is minimally invasive, preserves bone and tissue, and allows treatment of appropriately selected patients either in the operating room as done traditionally, or in the office using local anesthesia 2,3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of recent studies indicated less postprocedure narcotic use, earlier return to work, and fewer postoperative debridements after balloon dilation versus endoscopic sinus surgery and have established that in-office BCT use is very well tolerated by most patients. [1][2][3] Limitations of this technology, however, do exist, and include device failure, minimal anatomic effect (maximum balloon diameter is 7 mm), the reliance on wire-based technology for localization, difficulty ensuring that the correct anatomic outflow tract has been successfully dilated (i.e., creating a false passage into the maxillary sinus or dilating an accessory ostium as opposed to dilating the natural ostium), and the inability to visualize into the sinus cavity after dilation or to remove tissue. Further, the long-term sequelae, if any, of fracturing bony lamella and leaving them in situ remains unclear.…”
mentioning
confidence: 99%
“…The study design and procedures to week 24 have been described previously 1 ; this report will focus on follow-up through 1 year. In brief, all patients enrolled in the study were diagnosed with CRS as defined by the American Academy of OtolaryngologyHead Neck Surgery Clinical Practice Guideline, 2 and all patients had planned endoscopic sinus surgery (ESS) prior to being considered as candidates for the study.…”
Section: Patients and Study Designmentioning
confidence: 99%